2021
DOI: 10.1039/d1ra07514d
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterostructure Cu2S/Ni3S2 coral-like nanoarrays on Ni foam to enhance hydrogen evolution reaction in alkaline media

Abstract: We fabricated a heterostructure Cu2S/Ni3S2 nanosheet array, which can accelerate charge transfer and provide more active sites. This work provides a promising non-noble metal electrocatalyst for water splitting under alkaline conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Sulfuration does not damage the structure of the material and makes the surface of the smooth nanorod array rough. The rough surface structure is mainly due to the outward diffusion of S 2− and Cu + within the CF, which exposes more active sites 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfuration does not damage the structure of the material and makes the surface of the smooth nanorod array rough. The rough surface structure is mainly due to the outward diffusion of S 2− and Cu + within the CF, which exposes more active sites 49 …”
Section: Resultsmentioning
confidence: 99%
“…The rough surface structure is mainly due to the outward diffusion of S 2− and Cu + within the CF, which exposes more active sites. 49 The composition of the Cu(OH) 2 /Cu 2 S catalyst was analyzed by EDS. Figure 2A shows the SEM image of the Cu(OH) 2 /Cu 2 S sample, and Figure 2B−E shows the elemental scanning image of the Cu(OH) 2 /Cu 2 S sample.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…11 It was reported that alloying of Ir with transition metals like Pd, Ni, and Mo can enhance the catalytic activity by achieving an optimal balance between the hydrogen binding energy (HBE) and the hydroxide binding energy (OHBE). [19][20][21][22] Herein, a precursor route was designed for the synthesis of Ir-Ni/NiO/C products, whereby Ir nanoclusters were immobilized onto the generated Ni/NiO/C support derived from the metal-organic framework precursor. In the trinary support, the involved Ni would modulate the hydrogen binding energy, while the NiO can provide sites for the adsorption of OH species.…”
Section: Introductionmentioning
confidence: 99%
“…11 It was reported that alloying of Ir with transition metals like Pd, Ni, and Mo can enhance the catalytic activity by achieving an optimal balance between the hydrogen binding energy (HBE) and the hydroxide binding energy (OHBE). 19–22…”
Section: Introductionmentioning
confidence: 99%
“…Figure S4 SEM images after reaction. References [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%